MEMAHAMI KONSEP MAQÄÅID AL-SYARIAH DALAM FILSAFAT HUKUM ISLAM - Hasbi, Muhammad (Pasca Sarjana STAIN Watampone, 2014)
MaqÄÅid al-syariah is target and meaning desired by syara in specifying orÂ it all or most his lawses, or target oves and specified secret God in each God law. Thus, MaqÄÅid al-syariah is existing secret and target and desired God in specifying, ad for as a whole and some of laws of God. Target of syariah, at the core of is to look after kindliness of human being and obviate badness, either in world and in eternity/the beyond.Â Â Â Â Â Â Â Â Â Â Â Theory of maqÄÅid al-syariah, becoming fulcrums the core important is kindliness of human being in eternity/the beyond and world. This matter, new earn isnt it if five fundamental element can be realized and looked after. Ad for fundamental element, is to look after religion, soul, mind, clan and look after estae